2015
DOI: 10.24114/genre.v4i1.3958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group Investigation Method on Students’ Writing Achievement

Abstract: The objective of the study was to find out the effect of Group Investigation method on students’ writing achievement on narrative text. The study was conducted by using experimental research design. The population of this study was eight classes of the eleventh grade students of SMA Negeri 1 Kotapinang. The samples were taken by using clustering technique and two of the eight classes which was consisted of 60 students used as the samples, one class as experimental group and the other class as control group. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Hence, the researcher rejects the null hypothesis, which assumed no difference between learners taught with group investigation and those taught with the lecturebased approach. The study findings that showcased a superior concept mastery performance for learners taught using the group investigation method is congruent with previous studies (Adiansyah et al, 2017;Baki et al, 2010;Girsang, 2014;Parchment, 2009;Tran & Lewis, 2012a. The above-cited studies revealed that when learners are taught using a group investigation instructional approach, they perform better on their concept mastery skills than those taught with the traditional lecture approach.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Hence, the researcher rejects the null hypothesis, which assumed no difference between learners taught with group investigation and those taught with the lecturebased approach. The study findings that showcased a superior concept mastery performance for learners taught using the group investigation method is congruent with previous studies (Adiansyah et al, 2017;Baki et al, 2010;Girsang, 2014;Parchment, 2009;Tran & Lewis, 2012a. The above-cited studies revealed that when learners are taught using a group investigation instructional approach, they perform better on their concept mastery skills than those taught with the traditional lecture approach.…”
Section: Discussionsupporting
confidence: 89%
“…The Group investigation method has been found to supersede lecture-based instruction in improving learners' academic performance and learning. Previous studies on group investigation versus lecture-based instruction revealed that the experimental group exposed to the group investigation outperformed the lecture-based instruction group in their achievements in literature and language learning, higher assessment average, reading comprehension, learning mathematics, and transfer performance in various subject areas (Baki et al, 2010;Girsang, 2014;Parchment, 2009;Slavin, 2011). Other previous studies also found a significant correlation between group investigation and effective outcome, higher cognitive outcome, motivation, transfer, and increase in social communications compared to the lecture-based teaching identified to be less effective in promoting higher cognitive outcome, motivation, transfer, or social communication; though, some educators continue to use the lecture method (Slavin, 2011;Tran & Lewis 2012a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation